Medication Reconciliation Clinical Case - Demonstration - Kelly Karpa; Paul Haidet (Association of American Medical Colleges, 2012)
Abstract Introduction This medication reconciliation clinical case demonstration is used as a classroom instructional tool to assist students in developing a methodology for critically analyzing medications when conducting medication reconciliation, particularly those conducted when patients transition across care settings. Methods A number of medication errors have intentionally been built into the case. In the classroom, students are asked to identify the medication-related problems. After working independently, we discuss their responses as a group. Following the classroom session, students reconcile medications with individuals on their patient panel. At the conclusion of the course, students independently complete a patient case, similar to one that is presented in class, to assess their competency in identifying and resolving medication-related problems. Results Students were asked to rate their opinion of this session as being "helpful and educational." Using a 5-point Likert scale where 1 = strongly disagree and 5 = strongly agree, the mean rating given by students that responded (n = 11) was 4.18. Discussion Through use of this case as an instructional method, along with the accompanying medication framework and tools provided to the students, student competency at identifying medication-related problems increased substantially in a way that was directly relevant to patient care.